Development of enhanced sensitivity protocols on the RapidHIT™ 200 with a view to processing casework material. Issue 4 (July 2019) - Shackleton, David; Pagram, Jenny; Andrews, Nicholas; Malsom, Simon; Ives, Lesley; Vanhinsbergh, Des
Abstract: The RapidHIT™ 200 device from IntegenX® provides a sample-to-profile platform that is capable of processing a variety of sample types. In this study we review the sensitivity of the 'Run Other' protocol for processing crime stain type samples containing various input quantities of DNA using the AmpFℓSTR® NGMSElect™ Express PCR Amplification Kit cartridges available from IntegenX®. The range of DNA inputs which achieved useable results were not as desired and therefore various enhancements to the instruments extraction processes were investigated. These studies showed an improvement in the range of DNA input templates that could by processed on the RapidHIT™ 200 by using the enhanced methods and resulted in three new run protocols. Highlights: Development of RapidHIT 200 with NGMSElect Express for crime stain type samples Creation of novel Instrument protocols to extend range of DNA input templates Improved range of DNA inputs on RapidHIT 200 with NGMSElect Express